2003
DOI: 10.1021/la034435m
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Multicomponent Nanosize Clusters on Solid Surfaces

Abstract: We discuss the kinetics of multicomponent liquidlike clusters adsorbed onto solid surfaces. In this work, the rate expressions governing the growth and decay of surface clusters coupled to a two-dimensional gas phase are derived based on previous treatments of unary systems. General expressions are presented for the equilibrium partial pressures, the monomer evaporation rates, and the monomer capture rates. The composition dependence of the rate expressions is accomplished using the theory of real solutions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…At equilibrium with a single cluster (N,x), the density is uniform in keeping with Fick's law, J i ϭϪDٌ i ϭ0. In a previous report, 27 we have shown that the equilibrium partial pressures surrounding a binary cluster are remarkably well described by a generalization of the Gibbs-Thomson formula,…”
Section: A Rate Constant Expressionsmentioning
confidence: 79%
See 2 more Smart Citations
“…At equilibrium with a single cluster (N,x), the density is uniform in keeping with Fick's law, J i ϭϪDٌ i ϭ0. In a previous report, 27 we have shown that the equilibrium partial pressures surrounding a binary cluster are remarkably well described by a generalization of the Gibbs-Thomson formula,…”
Section: A Rate Constant Expressionsmentioning
confidence: 79%
“…͑2.7͒, either the evaporation or capture rates may be specified, thereby giving both sets of rates. In previous work, 27 we have undertaken large-scale numerical simulations of the evaporation rates that were found to be well represented using fairly simple expressions. Numerical Monte Carlo simulations 19,31,32 on model unary systems indicated that the scaling of the evaporation rates with cluster size shows a very noticeable deviation from the naive expectation, R i e (N,x A )ϰ2r, even for clusters Nϳ100 000.…”
Section: ͑25͒mentioning
confidence: 99%
See 1 more Smart Citation